Cohort Communities in Higher Education: The Best Example of Adult Education - Paula A. Brooks (Adult Education Research Conference, 1998)
Cohort groups facilitate relationships that encourage learning and act as a support for individuals. The underlying philosophy of a cohort is that learners become empowered and have a sense of ownership for their academic development. A sense of respect and collegiality were the most important outcomes and experiences in the cohort groups studied.